2012
DOI: 10.1177/147323001204000131
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD27 on B Lymphocytes in Patients with Primary Hepatocellular Carcinoma

Abstract: OBJECTIVES: Hepatitis B virus (HBV) replicates in the liver and can lead to hepatocellular carcinoma (HCC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
(30 reference statements)
3
15
0
Order By: Relevance
“…Multiple mechanisms have been put forward to expli cate the decreased functioning of NK cells and their association with cancer and cirrhosis of the liver, including fibrotic damage to NK cells [30] , phagocytic uptake of NK to B cells during germinal center reactions in secondary lymphoid tissues and function to support Bcell activa tion, affinity maturation, and isotype switching, leading to the generation of memory B cells and longlived plasma cells [39] . Although only a few studies have focused on humoral immunity in HCC and its regulatory mechanisms, impairment of CD4 + Tfh cells has been indicated to influence the development of HBV-associated HCC [40] . A decreased proportion of CXCR5 + CD4 + Tfh cells was found to be associated with HCC disease progression.…”
Section: Nk Cellsmentioning
confidence: 99%
“…Multiple mechanisms have been put forward to expli cate the decreased functioning of NK cells and their association with cancer and cirrhosis of the liver, including fibrotic damage to NK cells [30] , phagocytic uptake of NK to B cells during germinal center reactions in secondary lymphoid tissues and function to support Bcell activa tion, affinity maturation, and isotype switching, leading to the generation of memory B cells and longlived plasma cells [39] . Although only a few studies have focused on humoral immunity in HCC and its regulatory mechanisms, impairment of CD4 + Tfh cells has been indicated to influence the development of HBV-associated HCC [40] . A decreased proportion of CXCR5 + CD4 + Tfh cells was found to be associated with HCC disease progression.…”
Section: Nk Cellsmentioning
confidence: 99%
“…A well-studied example of this phenomenon is the cytokine IL-10, a critical Th2 cytokine which blocks the activities of more inflammatory Th1 T-cell cytokines. IL-10 is greatly increased in the serum and tissue of patients with HCC; however, it is not uniformly present in patients with chronic liver disease without HCC, suggesting that IL-10 may be needed for immunosuppression in the established and progressing tumor [118120]. The chemokine CCL22 also expresses in a similar pattern with IL-10.…”
Section: Non-cellular Factors In the Hbv-associated Hcc Microenvironmentmentioning
confidence: 99%
“…For example, IL-6 plays important roles in tumor initiation but displays a lower level of expression in tumor tissue than in peritumoral tissue [114,115]. However, IL-6 is elevated in the serum of patients with HCC compared to patients with chronic liver disease or healthy controls, and continues to rise as HCC progresses [120124]. Another example is IL-18, a member of the IL-1 family of cytokines, which has been reported to be present at increasing levels in the serum of patients with HCC compared to patients with cirrhosis or healthy controls [125,126].…”
Section: Non-cellular Factors In the Hbv-associated Hcc Microenvironmentmentioning
confidence: 99%
“…All of these 15 genes mutated in significantly more CRC samples than what expected by chance given the background mutation rate of 1.2×10 –6 (Binomial distribution model, FDR<1%) [59] and 11 of these 15 genes also had copy number deletions in significantly more CRC samples than what expected by random chance given the background copy number alternation rate of 1.2×10 –2 (Binomial distribution model, FDR<1%) [60]. For example, CD53 and CD27 for B cell activation [52], [61] were altered in a total of 45 and 15 CRC patients with somatic mutations or copy number deletions, respectively. Several reverse DE genes, such as CD27, LTF and DOCK2, were also found to be significantly hypermethylated in CRC.…”
Section: Resultsmentioning
confidence: 94%
“…Using the IRIS database, we also found that the UC-CRC inconsistent DE genes were enriched in genes specifically expressed in B cells (P = 0.016). All of the 22 UC-CRC inconsistent DE genes in the “humoral immunity”, including Igα, CD53 and CD27 which play key roles in regulating B-cell activation and immunoglobulin synthesis to mediated humoral immunity [52][54], were upregulated in UC but downregulated in CRC, in accordance with the observation that the immune system is hyperactive in UC [55], and that resting B cells can suppress T-cell-mediated anti-tumor immunity in tumors to promote tumor development [56]. Notably, in the “humoral immunity”, there were several DE genes, such as surface receptor CD81 and transmembrane protein LEU13 localizated on B cell membrane surface, that were up-regulated in CRC in comparison with the normal control.…”
Section: Resultsmentioning
confidence: 99%